Transparent Oxyfluoride Nano-Glass Ceramics Doped with Pr3+ and Pr3+–Yb3+ for NIR Emission - Gorni, Giulio; Cosci, Alessandro; Pelli, Stefano; Pascual, Laura; Durán, Alicia; Pascual, M. J. (Frontiers in Materials, 2017)
Pr3+-Yb3+ co-doped oxyfluoride glasses and glass-ceramics (GC) containing LaF3 nanocrystals have been prepared to obtain NIR emission of Yb3+ ions upon Pr3+ excitation in the blue region of the visible spectrum. Two different compositions have been tested 0.1-0.5 Pr-Yb and 0.5-1 Pr-Yb, in addition to Pr3+ singly doped samples. The crystallization mechanism of the nano-glass-ceramics was studied by DTA revealing that it occurs from a constant number of nuclei, the crystal growth being limited by diffusion. HR-TEM demonstrated that phase separation acts as precursor for LaF3 crystallization and a detailed analysis of the chemical composition (EDXS) revealed the enrichment in RE3+ ions inside the initial phase separated droplets, from which the LaF3 crystals are formed. The RE3+ ions incorporation inside LaF3 crystals was also proved by photoluminescence measurements showing Stark splitting of the RE3+ ions energy levels in the glass-ceramic samples. Lifetimes measurements showed the existence of a better energy transfer process between Pr3+ and Yb3+ ions in the glass-ceramics compared to the as made glass, and the highest value of energy transfer efficiency is 59% and the highest theoretical quantum efficiency is 159%, obtained for glass-ceramics GC0.1-0.5 Pr-Yb treated at 620 ºC-40 h.